Characteristic and Performance of Ni, Pt, and Pd Monometal and Ni-Pd Bimetal onto KOH Activated Carbon for Hydrotreatment of Castor Oil - Wega Trisunaryanti; Triyono Triyono; Iip Izul Falah; Dwi Bagus Wicaksono; Satriyo Dibyo Sumbogo (Universitas Gadjah Mada, 2024)
The preparation of highly efficient hydrotreating catalysts has presented a significant challenge in the field of catalysis. In this study, chemically activated carbon (AC) was prepared using potassium hydroxide (KOH) as an activator and Merbau wood as a lignocellulosic source for the AC. The AC was then impregnated with mono-metallic species (nickel, platinum, and palladium) as well as a bimetallic NiPd combination. The results revealed that the optimal KOH impregnation weight ratio was determined to be 2:1, resulting in a remarkably high iodine value of 751.94 mg/g. Subsequently, AC was employed as a support material for the hydrotreating of castor oil. Among the catalysts tested, the NiPd/AC catalyst demonstrated superior performance, yielding a liquid fraction comprising 88.80 wt.%. Within this fraction, C5-C12 hydrocarbons accounted for 15.16 wt.%, alcohol compounds constituted 71.69 wt.%, while the remaining 0.87 wt.% consisted of other components. Furthermore, the NiPd/AC catalyst exhibited remarkable stability, as its performance remained largely unchanged even after being used three times consecutively. This finding suggests that coking had minimal impact on the active sites of the mentioned catalyst, indicating its robustness and potential for prolonged application.